COLORIMETRIC MEASUREMENTS OF COCOA BEANS (Theobroma cacao) - Charles C.E. Meulemans; Untung Surapati T.; Ardin Tjatjo (Indonesian Agency for Agricultural Research and Development, 2002)
A series of studies have been carried out to develop a simple, easy to use, and affordable device to measure the colour of cocoa beans. The present paper reports the development of the device based on colorimetric principles. An electronic device which enables cocoa smallholders to give an objective “onefigure” indication of the quality of their cocoa beans was described. A sensor was constructed which contained a red light emitting diode (LED) illuminating the target and a silicon photodiode detecting the reflected light. Because of the considerable difference in colour between dried unfermented and fermented cocoa beans, the differences in diffuse reflection of red light (660 nm) could be about 20 and very easy to measure. The method was checked with a spectrophotometer in the fixed mode at 660 nm, which revealed a high correlation coefficient. The sensor was combined with a microprocessor controlled electronic device for fast measurement of cocoa beans without any calculations which automatically counts the number of measured beans and gives the resulting average reflection value.